The Influence of Employee Engagement and Employee Well Being on Company Reputation in Cleaning Service Companies - Mitrano, Agus; Febriyati, Dhama Tri (Talent: Journal of Economics and Business, 2024)
Employee welfare and employee engagement are one of the assessments or factors that can indicate that a company has engaged employees and the welfare provided by the company by providing health insurance, incentives, career ladders and others provides confidence to all employees that they are happy and proud to be in a large company and guarantees all the interests of its employees so that the company's reputation becomes the most important part for employees and the development of the company in the future. The research sample in the study amounted to 100 employees with stratified random sampling. The variables used to indicate employee engagement factors are Leadership, compensation, organizational culture. Other latent variables are employee engagement and employee performance. The variables were analyzed using Structural Equational Modeling-Partial Least Square (SEM-PLS). From the results of the study, it was found that Employee Well Being has positive and significant results on both employee engagement and Company reputation. Practically, the results of this study provide recommendations for service companies to prioritize policies that support employee Employee Well Being, such as health insurance, rewarding, incentives, career ladders and work-life balance programs. This is expected to increase the agility of the workforce in responding to changing customer needs. Theoretically, this study contributes to the literature on factors that influence Company Reputation, especially in the service sector, by emphasizing the significant role of Employee Well Being compared to Employee Engagement. Further research is recommended to explore other aspects that can influence Company Reputation, such as Leadership Model and Operational Excellence.